The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.20515/otd.459018
|View full text |Cite
|
Sign up to set email alerts
|

Fibromiyalji Sendromunda D Vitamin Düzeylerinin Değerlendirilmesi

Abstract: Özet: Bu çalışmanın amacı, fibromiyalji sendromu olan hastalarda 25(OH)D düzeyini değerlendirmek ve hassas nokta sayısı ile 25(OH)D düzeyi arasındaki ilişkiyi araştırmaktı. Bu retrospektif çalışmaya, 2016-2017 yılları arasında fibromiyalji tanısı almış 61 hasta dahil edildi. Hastaların demografik verileri, 25(OH)D düzeyleri, hassas nokta sayıları değerlendirildi. Hastalar 25(OH)D düzeyleri göre; D vitamini eksikliği (<20 ng/ml), D vitamini yetersizliği (20-30 ng/ml) ve normal D vitamini düzeyi olarak (>30 ng/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Vitamin D has been extensively studied in relation to fibromyalgia, with many studies reporting low levels of this vitamin in individuals with the condition [8][9][10]. Akar et al [8] suggested that patients with vitamin D levels below 25 ng/ml may be more prone to experiencing pain and developing fibromyalgia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D has been extensively studied in relation to fibromyalgia, with many studies reporting low levels of this vitamin in individuals with the condition [8][9][10]. Akar et al [8] suggested that patients with vitamin D levels below 25 ng/ml may be more prone to experiencing pain and developing fibromyalgia.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Özcan et al [9] observed lower levels of 25-hydroxy vitamin D in 60 patients with fibromyalgia compared to 30 healthy controls. Özgen et al [10] reported that only 11.48% of the patients with fibromyalgia had normal vitamin D levels (above 30 ng/ml).…”
Section: Introductionmentioning
confidence: 99%